“Selective memory”: A Museum and Its Past - Bruni, Ilaria (Actual Problems of Theory and History of Art, 2022)
“Selective memory” of the past, borrowing the definition from cognitive psychology and neuroscience, represents a phenomenon closely tied to the history of classical archaeology and the antiquarian, specifically within Italian museum studies, as a cultural-ideological result of 19th and 20th century historical events.A research recently undertaken into the current situation of museums pertaining to a subregional district of southern Latium, the region of central western Italy of which Rome is the county seat, constituted an opportunity for comparison based on the analysis of some indicators, both aesthetical and technical: museological and museographical approaches, management issues, exhibition design, and communication strategies. A common thread is a perpetuation of bygone ideological and propaganda symbols as nostalgia for the past and the reactivation of historical, political, and anthropological phenomena.As a case study the Archaeological Civic Museum of Terracina, a city 100 kilometers south of Rome, has been chosen, in consideration of its long history and the possibility to assist to the evolution of the fittings and locations from 1894, the year of foundation, until today, by dint of photos, inventories, and period letters. The central theme of criterion for selecting the archaeological material to be exhibited has been, since the beginning, the past that we choose to tell. This “selective memory” is identifiable in the different treatment reserved to single objects: some have been collected and preserved, some have been scattered, some have been perceived as unrepresentative, and thus deemed unworthy of display or narration, and stored in depots. The museum has consequently selected only certain aspects of the past of its community, which is almost entirely related to its Late Roman Republican and Imperial period, an attitude which in the literature is frequently referred to as “Romanolatry”. The cult of the “white archaeology” removes from consideration the material culture of everyday life, of prehistoric, protohistoric, late antique, medieval, and Renaissance phases, even when well documented. Is the museum a place of oblivion or a place of memory?
Keywords: classical archaeology; museum studies; antiquarian; nostalgia; propaganda; memory